Detection of hepatitis B virus DNA in sera from 18 alcoholic carriers of "anti-HBc alone" and response to a single dose of hepatitis B vaccine - Oliveira,Luiz Carlos Marques de (2008)
To evaluate the possibility of occult hepatitis B virus (HBV) infection in alcoholics carriers of "anti-HBc alone", and to verify the behavior of this serological pattern after a single dose of hepatitis B vaccine, 18 alcoholics who had this serological profile were evaluated by the polymerase chain reaction method, and 17 of them were vaccined. All were negative for HBV DNA. Nine (52.9%) of those vaccined had anamnestic response, mainly those with positive anti-HBe (8/10; 80%). "Anti-HBc alone" was compatible with low levels of anti-HBs in half of the patients, and probably with false positive results for anti-HBc in the others.